2007
DOI: 10.1891/106137407783095775
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Assessment of the Postpartum Depression Predictors Inventory–Revised

Abstract: Identification of women at risk for postpartum depression requires reliable and valid assessment indices. The purpose of this article is to describe the psychometric properties of the Postpartum Depression Predictors Inventory-Revised (PDPI-R). Psychometric assessment of the PDPI-R was conducted in conjunction with the Centers for Epidemiologic Studies Depressed Mood Scale, and the Edinburgh Postnatal Depression Scale, using data from 139 pregnant women who were followed for 8 months after birth. The prenatal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 28 publications
3
28
0
2
Order By: Relevance
“…European Portuguese postnatal version of the PDPI-R. Consistent with previous studies (Ikeda & Kamibeppu, 2013;Records et al, 2007), the findings supported the validity and reliability of the PDPI-R postnatal version as a screening instrument for predicting PPD based on past and current risk. Particularly, the results offered preliminary evidence about the predictive validity of the postnatal version using the EPDS as the gold standard.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…European Portuguese postnatal version of the PDPI-R. Consistent with previous studies (Ikeda & Kamibeppu, 2013;Records et al, 2007), the findings supported the validity and reliability of the PDPI-R postnatal version as a screening instrument for predicting PPD based on past and current risk. Particularly, the results offered preliminary evidence about the predictive validity of the postnatal version using the EPDS as the gold standard.…”
Section: Discussionsupporting
confidence: 87%
“…Contrary to the original studies on the PDPI-R (Beck et al, 2006;Records et al, 2007) but consistent with recent validation studies, our preliminary analyses demonstrated acceptable cut-off points for the postnatal version of the instrument. When using a cut-off score above 9 on the EPDS, we suggest the same PDPI-R cut-off score of 5.5 that was observed in the postnatal Italian validation (Oppo et al, 2009) despite the fact that these authors used different criteria to diagnose PPD.…”
Section: Discussionsupporting
confidence: 78%
“…3. Risk factors associated with PME were measured using the Revised Postoperative Depression Inventory (PDPI-R) (Records, Rice, & Beck, 2007). Typically, the instrument is used to evaluate risk factors for postpartum depression (PPD).…”
Section: The Maternal Efficacymentioning
confidence: 99%
“…Developed as a brief measure to identify women at risk for PPD, the PDPI-R was shown to have good predictive construct and concurrent validity among a sample of 139 pregnant women who were followed for 8 months after birth. 18 Being a Mother Scale (BaM-13). 19 The BaM-13 is a 4-point Likert-style self-report measure developed to evaluate women's emotional adjustment to motherhood for women with children ranging from infants to preschool age.…”
Section: Postpartum Depression Predictors Inventory-revised (Pdpi-r)mentioning
confidence: 99%